Use of a Bluetooth tablet‐based technology to improve outcomes in lung transplantation: A pilot study. Issue 12 (13th July 2020) - Schenkel, Felicia A.; Barr, Mark L.; McCloskey, Chris C.; Possemato, Tammie; O'Conner, Jeremy; Sadeghi, Roya; Bembi, Maria; Duong, Marian; Patel, Jaynita; Hackmann, Amy E.; Ganesh, Sivagini
Abstract : The impact of remote patient monitoring platforms to support the postoperative care of solid organ transplant recipients is evolving. In an observational pilot study, 28 lung transplant recipients were enrolled in a novel postdischarge home monitoring program and compared to 28 matched controls during a 2‐year period. Primary endpoints included hospital readmissions and total days readmitted. Secondary endpoints were survival and inflation‐adjusted hospital readmission charges. In univariate analyses, monitoring was associated with reduced readmissions (incidence rate ratio [IRR]: 0.56; 95% confidence interval [CI]: 0.41‐0.76; P  < .001), days readmitted (IRR: 0.46; 95% CI: 0.42‐0.51; P  < .001), and hospital charges (IRR: 0.52; 95% CI: 0.51‐0.54; P  < .001). Multivariate analyses also showed that remote monitoring was associated with lower incidence of readmission (IRR: 0.38; 95% CI: 0.23‐0.63; P  < .001), days readmitted (IRR: 0.14; 95% CI: 0.05‐0.37; P  < .001), and readmission charges (IRR: 0.11; 95% CI: 0.03‐0.46; P  = .002). There were 2 deaths among monitored patients compared to 6 for controls; however, this difference was not significant. This pilot study in lung transplant recipients suggests that supplementing postdischarge care with remote monitoring may be useful in preventing readmissions, reducing subsequent inpatient days, and controlling hospital charges. A multicenter, randomized control trial should be conducted to validate these findings. Abstract : The use of a novel remote monitoring platform to supplement the postdischarge care of lung transplant recipients reduces hospital readmissions, total readmission days, and readmission charges.